Rancang Bangun Sistem Parkir RR V.7.2 Menggunakan Metode Pengembangan SDLC (Software Development Life Cycle) Waterfall Pada PT. Tri Alfa Sinar Mandiri - Nanda Diaz Arizona; Yulia Yulia (Jurnal Sistem Informasi Akuntansi, 2025)
This research aims to design and develop a new parking system, the RR Parking System V.7.2, at PT. Tri Alfa Sinar Mandiri using the Waterfall software development method. The current parking system still has several weaknesses, such as inefficient monitoring processes and a lack of real-time data processing features. Therefore, this research proposes a solution through a developed system that can improve parking management efficiency and provide users with the convenience of displaying parking status more accurately. The Waterfall method was chosen for this system development because of its systematic and structured approach, allowing each stage to be carried out sequentially, from requirements analysis and system design to software development and testing and implementation. During the requirements analysis stage, problems and functional and non-functional requirements of the parking system are identified. The design stage includes the creation of a simple and easy-to-use system architecture and user interface. Software development is conducted using a programming language that supports database integration and a real-time parking monitoring system